Consumer Protection Due to Disclaimer Clause in Internet Site - Vitarani, K.; Rumawi, Rumawi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
A unilateral agreement that contains a transfer of responsibility or known as a disclaimer clause is deemed to be in conflict with the provisions of Law No. 8 of 1999 concerning Consumer Protection in article 18, an agreement which contains limits on responsibility is also contrary to the law of agreements where this is considered to have deviated or there is no compliance or conformity with one of the conditions for the validity of an agreement, namely "a legal cause", besides this having a negative impact on legal development and the health of the economy, law enforcement should be more detailed and firm regarding this matter. This research aims not to ignore a provision and as an enlightenment for legislative institutions to focus more on problems that are often overlooked, especially on law enforcement. The formulation of the problem is about the nature of the disclaimer clause according to contract law, consumer protection law and its impact in the future for business actors and consumers as a form of material or basic knowledge of legal certainty and the impact of the inclusion of the disclaimer clause. The method used in research is a type of normative legal research. The validity of an agreement according to the Civil Code must fulfill the four conditions stated in article 1320 of the Civil Code. The inclusion of standard clauses on internet sites remains based on the law of agreements in the Civil Code. Meanwhile, the inclusion of unilateral agreements on internet sites in consumer protection law is considered valid as long as it does not violate the rules in article 18. In conclusion, there is no truth in the inclusion of a disclaimer if viewed from consumer protection law, and in assessing the meaning and definition of a disclaimer which is clearly against the rules, its inclusion is considered does not conform to the requirements in article 1320 of the Civil Code regarding the existence of a legal cause. The impact of including the disclaimer clause will result in legal problems for consumers and business actors as well as a lack of justice.